Temporary Fixes, Permanent Problems: Implications of the Growing Reliance on Liminal Status in U.S. Immigration Policy. - Orrenius, Pia M.; Zavodny, Madeline (Southern Economic Journal, 2025)
Record migrant inflows in the post‐pandemic period have brought renewed attention to the problems associated with temporary fixes to immigration policy. In response to surges of vulnerable migrants and because of the failure to enact legislative change, multiple presidential administrations devised new ways to enable millions of migrants to remain in the United States for years and even indefinitely without lawful permanent resident status. This lack of permanent status is costly to migrants, employers, and the broader economy. It deters investments in human and physical capital, leading to a misallocation of resources and subpar productivity growth. It also leaves migrants vulnerable to policy changes triggered by a change in administration, most recently the threat of mass deportations. Solutions require Congress to address the coming demographic winter with, among other policies, higher volumes of legal immigration and more opportunity to earn permanent residence and a pathway to U.S. citizenship.